CLINICAL EVALUATION AND PATCH TESTING IN HAND ECZEMA - Vijender Kumar (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Due to its widespread etiology, protracted cause, remissions and exacerbations, resistance to therapy, and unique anatomical features of the palmer skin, hand eczema is a common and frequently painful skin disorder. Presumably the nineteenth century saw the first description of it. It is a common issue that affects people in a variety of professions. Hand eczema is likely to appear in between 2% and 10% of people at some point in their lives. The majority of hand eczema cases have a multifactorial etiology, in which the eczema is triggered and maintained by exogenous variables in people who are predisposed to such processes because of endogenous factors. The proper therapy of hand eczema requires the identification and avoidance of external competitors. A trusted technique for identifying allergic contact dermatitis is patch testing. To confirm the diagnosis, patients with a history and clinical picture consistent with contact dermatitis are re-exposed to potential allergens under controlled circumstances.Aim: To assess the clinical profile of hand eczema in the patient, to perform a patch test in relevant cases, and to find out the most common sensitizers in them. Material and Method: This cross-sectional investigation was conducted in the dermatology department. A total of 100 people with hand eczema visited the dermatology department's outpatient clinic. After receiving informed consent, each patient's complete medical history—including their occupation, the length of their complaints, pruritus, their history of personal or occupational chemical exposure, their history of atopy, recurrences, aggravating factors, and their treatment history—was recorded in the proforma. The ultimate diagnosis, course of treatment, and specific examination findings with regard to the morphology and region of involvement were also recorded. Prior to doing the patch test, each patient received thorough instruction on patch testing.Results: Out of 100 patients, major occupations among them were housewives 27 (27%), followed by masons 22 (22%), farmers 10 (10%), mechanics 7 (7%), students 5 (5%), software engineers 6 (6%). Hyperkeratotic palmar eczema was the most common morphology observed in 53 of the patients (53%) followed by 19 fingertip eczema (19%), 11 discoid eczema (11%), 7 wear and tear dermatitis (7%), 5 pompholyx (5%), 5 recurrent focal palmer peeling (5%). Nickel was the most common allergen in our study 27 (27%) followed by potassium dichromate 10 (10%), parthenium 6 (6%), cobalt and nickel 3(3%), fragrance mix, formaldehyde and black rubber mix showed positive reaction in two patients eachConclusion: In our study, patients with hand eczema tended to be between the ages of 21 and 60. Hand eczema is more likely to appear among mechanics, housewives, masons, and farmers. The most prevalent morphological kind of eczema was hyperkeratotic palmar eczema, which was followed by fingertip eczema. Nickel patch test positivity was most frequently noted, particularly among housewives. The most prevalent allergy among masons is cement made with potassium dichromate. The majority of patients with pompholyx have a history of atopy. This particular variety of hand dermatoses may be made worse by the workplace.Keywords: Hand eczema, Morphological type, Patch test, Allergens, Occupation, Nickel, Potassium Bichromate.